Jewelry Morocco septaria. Gemological characteristics and mineral composition - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка)
Background. Septaria, comprising calcareous-clay nodules with calcite veins, are widely used as jewelry and ornamental materials. Septaria from Morocco represented on the world and Russian markets of jewelry and ornamental stones remain gemologically and mineralogically underexplored. In this article, the gemological characteristics and mineral composition of Morocco septaria, as well as the conditions of their formation, are described for the first time.Aim. To determine the gemological characteristics and mineral composition of Morocco septaria, as well as their formation conditions. To conduct their comparison with septaria from other regions of the world.Materials and methods. The author studied the assortment of Morocco septaria presented at international and Russian exhibitions. A collection (15 samples) representing the main decorative septarium varieties was compiled. The materials underwent determination of microhardness, density, luminescence (10 samples), optical-petrographic analysis (4 sections), quantitative determination of mineral and chemical composition (2 samples), electron probe studies (2 samples).Results. The septaria were found to consist of (wt %): quartz — 38, goethite — 16, chlorite (shamosite) — 28, kaolinite — 6, siderite — 5, dolomite — 4, calcite — 1, pyrite, zeolite, apatite, hydrosludes less than 1. Dispersed inclusions of leucoxene, barite, and microcline were discovered. The septarium veins consisted mainly of dolomite, quartz, chlorite with inclusions of siderite, calcite and pyrite. The Zn, Sr, and Ba impurities ranged within 0.01—0.05 wt %, while Cr, V, Ni, Cu, Rb, Zr, Y, and Pb ranged within 0.001—0.01 wt %. The mineral composition of the studied Morocco septaria was found to differ significantly from that of septaria in other regions of the world, where calcite plays a decisive role.Conclusion. Morocco septaria of small size (from 2 to 6 cm) are used as interior decorations and jewelry cabochons. The mineral and chemical (including micro-inclusions and impurities) composition of Morocco septaria was established for the first time, which allows their identification. The mineral composition of the septaria under study is associated with the regional low-temperature metamorphism, which altered the original, predominantly calcite composition.